Is Infection Prevention and Control Training Can Increase Knowledge and Compliance of Nurses? - Wati, Ni Made Nopita; Subyaktien, Elmy; Lestari, Tri Rahyuning; Pendet, Diah Pusparini; Rachmawati, Nunung; Juanamasta, I Gede; Aungsuroch, Yupin (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
One of the indicators of service quality at the hospital is Healthcare-Associated Infections (HAIs) that can be prevented by hand hygiene, which is a procedure for cleaning hands with soap water, or alcohol-based liquids. This study aimed to identify the effect of Infection Prevention and Control (IPC) training on the level of knowledge and compliance of five moments for hand hygiene in nurses at the Dharma Yadnya Hospital in Denpasar. This study used a pre-experimental one-group pre-post test without a control group design. The number of samples was 42 nurses with purposive sampling techniques that met the inclusion and exclusion criteria. The results showed that before training 26 nurses (61.9%) had a good level of knowledge, and after training, 41 nurses (97.6%) had good knowledge. With regard to compliance with five moments for hand hygiene, before training 22 nurses (52.4%) were not compliant, and after training 29 nurses (69%) imperfectly adhered to the procedure. Mandatory training in IPC influences the level of knowledge and adherence to the five moments for hand hygiene among nurses. Suggestions for hospitals to provide continuity of education related to IPC, monitor nurses' compliance behaviors of the five moments for hand hygiene, either by direct observation or electronically, and provide rewards and punishments for behavioral evaluations.